2022
DOI: 10.1007/s12560-022-09530-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus in Water Environments: A Systematic Review and Meta-analysis

Abstract: Hepatitis E virus (HEV) is responsible for acute hepatitis in humans, through foodborne, zoonotic, and waterborne transmission routes. This study aimed to assess the prevalence of HEV in water matrices. Six categories were defined: untreated and treated wastewater, surface water (river, lake, and seawater), drinking water, groundwater, and other water environments (irrigation water, grey water, reservoir water, flood water, and effluent of pig slaughterhouse). We searched PubMed, Web of Science, Global Index M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 107 publications
(86 reference statements)
0
22
0
Order By: Relevance
“…This finding aligns with previous studies that have identified contaminated water as a primary transmission route for HEV (21,22). The fact that a majority of the incident seroconversions were observed in individuals who consumed untreated or occasionally treated surface water further underscores the importance of water quality in HEV exposure The spread of HEV to the environment might pollute surface waters, which could act as the source of infection for both humans and animals (23). Moreover, the occurrence of HEV in different water environments, even in industrialized countries with sanitation and safe water supplies, has been documented, emphasizing the need for continuous monitoring and intervention (23).…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with previous studies that have identified contaminated water as a primary transmission route for HEV (21,22). The fact that a majority of the incident seroconversions were observed in individuals who consumed untreated or occasionally treated surface water further underscores the importance of water quality in HEV exposure The spread of HEV to the environment might pollute surface waters, which could act as the source of infection for both humans and animals (23). Moreover, the occurrence of HEV in different water environments, even in industrialized countries with sanitation and safe water supplies, has been documented, emphasizing the need for continuous monitoring and intervention (23).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis E virus (HEV): although we did not obtain positive results, HEV has been previously assessed in water matrices, including untreated and treated wastewater, surface water (river, lake, and seawater), drinking water, groundwater, and other water environments (irrigation water, grey water, reservoir water, flood water, and effluent of pig slaughterhouse) (Takuissu et al 2022). However, to our known, no research has focused on water sources predominantly used by wildlife.…”
Section: Mycobacterium Tuberculosis Complex (Mtc)mentioning
confidence: 91%
“…Human activities, such as intensive livestock farming and wastewater discharges, have also contributed to the degradation of the microbiological quality of groundwater, aquifers, and springs (Savio et al., 2018; Stevens et al., 2022; Takuissu et al., 2022). Fecal contamination infiltrates soils and reaches groundwater and aquifers, even at great depths.…”
Section: Current and Future Risks Of Spring Ecosystemsmentioning
confidence: 99%
“…Recent studies have indicated a general underestimation of aquifer contamination through enlarged cracks and fissures (Hartmann et al., 2021). Pathogenic bacteria, such as Escherichia coli and other coliforms, and enteric viruses like Norovirus , Rotavirus , hepatitis A and E viruses, as well as protozoa like Cryptosporidium and Giardia , are increasing, compromising springs as secure freshwater resources (An & Breindenbach, 2005; Aqso et al., 2014; Blanco et al., 2017; Davidson et al., 2016; Murphy et al., 2017; Ryu et al., 2019; Takuissu et al., 2022).…”
Section: Current and Future Risks Of Spring Ecosystemsmentioning
confidence: 99%